Implementasi Kriteria Dalam Metode Weighted Product Untuk Menentukan Santri Terbaik Di Pondok Pesantren Nafidatunnajah - Andrian Hidayat; Ade Napila (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
A santri is an individual who undergoes Islamic education in a boarding school known as a pondok pesantren, typically residing there until the completion of their studies. Upon graduation, some santri voluntarily dedicate themselves to serve as staff in the pesantren. At Yayasan Nafidatunnajah Islamic Boarding School, the selection of the best santri is a regular activity conducted each academic period to encourage students to improve their academic achievements and moral conduct. Outstanding students are not only recognized but also awarded by the foundation. However, the selection process faces challenges due to the large number of assessment criteria and the lack of standardized weightings for each criterion. Currently, no decision support system is in place to assist in making objective and efficient evaluations. This study aims to develop a decision support system using the Weighted Product (WP) method. WP works by multiplying the values of each attribute, which are first exponentiated by the respective criterion weight. This ensures that the results align with the preferences and priorities set by the institution. The proposed system is expected to support the pesantren in selecting the best santri more effectively and objectively. The final output of this research is intended for publication in a national academic journal.